Measuring and analyzing the impact of public government spending on economic growth in Iraq for the period 2004-2022 - Habeeb, Adnan (The Gulf Economist, 2024)
Abstract: General government spending has a significant impact on achieving a number of goals that the state seeks to reach , and those goals fall under the names of achieving economic balances or addressing emergency crises and imbalances that the economic sectors are exposed to, and those goals or objectives are achieved through state spending on various economic activities and Public Utilities, whether service or production, and the impact of general government spending directly on economic growth indicators, including the GDP index and the average per capita output index and their growth rates , Therefore, the research focused on analyzing and measuring the impact of large public spending in bringing about developments at the level of economic growth in Iraq and measuring the extent of its contribution to achieving economic development rates within the mentioned, within the said period.